1986
DOI: 10.1016/0304-405x(86)90026-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-trading, market making, and estimates of stock price volatility

Abstract: We examine the effects of market making and intermittent trading on estimates of stock price volatility. When observed price changes are correctly tied to a stock's true price dynamics, it is found that nontrading per se causes a loss of efficiency but no bias in traditional volatility estimates. Nontrading induces substantial inefficiency in the extreme value estimator of volatility which it biases downward. Market making's effects add to the nontrading-induced inefficiency in the traditional estimator, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Therefore, the EV estimators are more appropriate even for the daily volatility estimation. The early literature generally confirms a negative bias in EV estimators, as compared to historical volatility (for instance, Garman & Klass, 1980;Marsh & Rosenfeld, 1986;Wiggins, 1991Wiggins, , 1992. We find them positively biased compared to the historical volatility for daily estimations.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, the EV estimators are more appropriate even for the daily volatility estimation. The early literature generally confirms a negative bias in EV estimators, as compared to historical volatility (for instance, Garman & Klass, 1980;Marsh & Rosenfeld, 1986;Wiggins, 1991Wiggins, , 1992. We find them positively biased compared to the historical volatility for daily estimations.…”
supporting
confidence: 54%
“…Early empirical studies on these estimators (Wiggins, 1991(Wiggins, , 1992 confirmed their relative efficiency in estimation but raised doubts about their bias, particularly for less liquid assets. Marsh and Rosenfeld (1986) also reported a bias in these estimators due to discrete trading. However, these studies used historical volatility as the benchmark.…”
Section: Introductionmentioning
confidence: 90%
“…The Parkinson (1980) estimator in particular contains little empirical bias relative to close-to-close volatility, suggesting the discrete-time and discrete-price trading problems discussed in Garman and Klass (1980) and Marsh and Rosenfeld (1986) are not particularly serious for an actively traded instrument with small price increments.…”
Section: Extreme-value Methodsmentioning
confidence: 96%
“…In spite of these appeals, the strict assumptions of log-normal asset returns distribution and continuous trading have been a big obstacle for attracting enough attention. For instance, Marsh and Rosenfeld [18] and Wiggins [27][28] show that the analyses using range volatility estimators succeed in enhancing efficiency but fail to reduce biasness. The main cause of this finding is the low liquidity of the assets under their studies which lead to the violation of continuous trading assumption.…”
Section: Introductionmentioning
confidence: 99%